EVALUATION OF SUSCEPTIBILITY OF REFERENCE STRAINS OF MICROORGANISMS TO THE COMBINED ACTION OF ESSENTIAL OILS AND MEXIDOL - Bobrova, N.A.; Vazhnichaya, E.M.; Loban, G.A.; Devyatkina, T.A.; Lugovaya, L.A.; Balyuk, O.Ye.; Bashtovenko, O.A. (World of Medicine and Biology, 2021)
The susceptibility of the reference strains S. aureus ATCC 25923 and E. coli ATCC 25922 to 14 essential oils and their combinations with mexidol (ethylmethylhydroxypyridine succinate) was studied using the disk diffusion method. It was shown that a combination of all essential oils (with the exception of eucalyptus and ginger) with mexidol increases the susceptibility of S. aureus ATCC 25923 to these agents, with the most pronounced effect being observed with oils of lemon, lavender, fir, and rose. The susceptibility of E. coli ATCC 25922 to essential oils of cinnamon, mint, tea tree, rose, eucalyptus, cloves, and sage significantly increases when combined with mexidol, and this effect is the most pronounced when using combinations of mexidol with rose, eucalyptus, and clove oils. The discovered ability of mexidol to increase the susceptibility of microorganisms to essential oils can be a basis for the development of pharmaceutical compositions with these substances in which an enhanced antimicrobial effect will accompanied by an antioxidant activity and low toxicity.